Evaluation of Changes in the Quality of Life Using the U22 Questionnaire after Cavotricuspid Isthmus Ablation - Yakushev, Andriy V.; Podluzhny, Mykhaylo S. (Ukrainian Journal of Cardiovascular Surgery, 2023)
Atrial tachyarrhythmias are the most common forms of heart rhythm disorders. According to literature sources, isolated atrial flutter (AFL) is observed in 88 people per 100,000 population. Most quality-of-life assessment methods have been developed and used primarily to assess atrial fibrillation. In this context, the U22 questionnaire becomes a significant protocol aimed at quantifying paroxysmal symptoms associated with tachyarrhythmias. The aim. To evaluate changes in the quality of life in patients with typical AFL after radiofrequency ablation (RFA) and bidirectional conduction block through the cavotricuspid isthmus. Materials and methods. The study is based on the analysis of the results of the treatment of a group of 135 patients at the National Amosov Institute of Cardiovascular Surgery of the National Academy of Medical Sciences of Ukraine in the period from 2014 to 2021. The patients had three follow-up examinations, which were subject to analysis and static processing: before RFA (n=135), after 1 month (n=122) and after 1 year (n=81). All the patients were interviewed concerning their arrhythmia-related symptoms, which were assessed according to the U22 protocol. Results. Before the procedure, the patients noted a low level of well-being (4.3±1.0 points). During the follow-up visit 1 month after RFA, the patients rated their general condition during this period at 8.9±0.7 points. The registered changes were statistically significant compared to the initial state (p<0.0001). Thus, the radical elimination of AFL led to rapid improvement in the psycho-emotional and physical condition of the patients as early as within 1 month. Similar changes were observed during the assessment after 1 year, when the patients assessed their condition at 9.3±0.7 points (p<0.0001); there was statistically significant difference compared to the initial condition and the results at the first follow-up examination. These results confirm the stability of the positive trend during the medium-term follow-up. Conclusions. The U22 questionnaire found symptomatic improvement in patients undergoing RFA of cavotricuspid isthmus. The U22 questionnaire can be considered as another, additional control tool for patients who underwent RFA. The peculiarity of its application is the specificity of the assessment of paroxysmal symptoms and complaints, which are specifically related to rhythm disturbances, and the possibility of a simple analysis of the dynamics for a long time after the intervention.